THE CONCEPT OF THE BLESSING OF KNOWLEDGE IN ISLAMIC EDUCATION: A PHILOSOPHICAL AND IMPLEMENTATIVE STUDY IN THE FORMATION OF ISLAMIC CHARACTER - Salibah Jaro’i; Khairuddin Lubis (Jurnal Bilqolam Pendidikan Islam, 2026)
This study examines the theory of the blessing of knowledge in Alwashliyah education as a philosophical and practical foundation in shaping Islamic character and educational values. The purpose of this study is to analyze the concept of blessed knowledge in Islamic educational traditions and its implementation in the educational culture of Alwashliyah institutions. This research uses a qualitative approach with a literature study method, examining various scientific sources such as books, journals, and educational documents related to Islamic education and Alwashliyah thought. The findings reveal that the theory of blessed knowledge in Alwashliyah education emphasizes sincerity, moral discipline, respect for teachers, and the integration of religious and social values. Knowledge is not only understood as intellectual achievement but also as a spiritual path that brings benefits to individuals and society. The implementation of this theory is reflected in character education, teacher exemplification, worship habits, and the strengthening of Islamic organizational values in schools and universities. The study concludes that the theory of blessed knowledge remains relevant in responding to contemporary educational challenges, especially amid the moral crisis and the dominance of materialistic educational orientations.